2016
DOI: 10.21786/bbrc/9.3/18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gel porosity and stiffness on culture of HepG2 cells encapsulated in gelatin methacrylate hydrogels

Abstract: Owing to in vivo applications, use of biodegradable three dimensional matrices to form implantable tissue constructs has increased in recent times. Gelatin methacrylate gel (GelMA) is one such versatile matrix compatible for cell culture and has potential of in vivo implantation. Physical and mechanical properties of these hydrogels are extremely crucial in modulating their rigidity, biodegradability and cellular compatibility. The present study involves testing stiffness and porosity of GelMA at high and low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…However, a decrease in HepG2 cell viability on day 3 and 7 of culture with considerably smaller spheroid size indicated that there was significant growth restriction on HepG2 cells when embedded in dECM-based scaffolds with a stiffness similar to cirrhotic liver. These findings are consistent with literature reports on reduced viability and growth in cancer cells cultured in stiff 3D hydrogels [9,36]. A further evaluation on the gene expression confirmed these results as attributed by the lower levels of the proliferation marker MKI67 , ALB , and AFP expression coupled with higher levels of the apoptosis marker CASP8 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, a decrease in HepG2 cell viability on day 3 and 7 of culture with considerably smaller spheroid size indicated that there was significant growth restriction on HepG2 cells when embedded in dECM-based scaffolds with a stiffness similar to cirrhotic liver. These findings are consistent with literature reports on reduced viability and growth in cancer cells cultured in stiff 3D hydrogels [9,36]. A further evaluation on the gene expression confirmed these results as attributed by the lower levels of the proliferation marker MKI67 , ALB , and AFP expression coupled with higher levels of the apoptosis marker CASP8 .…”
Section: Discussionsupporting
confidence: 92%
“…Traditional approaches to study HCC progression involved simply regulating 2D substrate stiffness, which, however, is not representative of the 3D mechanical environment in native liver and therefore could incur results inconsistent with those from 3D approaches [711]. Current studies examining the liver mechanical properties with 3D matrix models, however, do not reflect the clinically reported stiffness range and the microarchitecture of cirrhotic liver and thus provide less insightful results in understanding HCC progression under diseased conditions [9,12]. In addition to the importance of a relevant 3D mechanical environment, the biomaterial used to study cancer progression has also been shown to play an important role in regulating cancer growth and proliferation [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for the HepG2-laden constructs of the control group W0, a strong increase of both, the DNA content and the LDH activity, was observed over the cultivation period of 14 days, indicating cell proliferation and high metabolic activity of the cells within the Plasma-Alg-MC. This is in line with our previous study [22] and can be attributed to the fact that hepatic cells prefer and are better adapted to soft hydrogels [56] due to their natural microenvironment. [22,56] Interestingly, despite the good performance of the HepG2 in the control group W0, the most dramatic effect of cold storage was observed for these cells: Whereas on day 1 after printing, the cell numbers in the storage groups W1-W4 were comparable to the control group W0, very low cell numbers were detected on day 7 and 14 of cultivation.…”
Section: Discussionsupporting
confidence: 93%
“…Natural biopolymers such as chitosan and gelatin have been extensively used to fabricate 3D-hydrogels, which have shown promise as scaffolds for several soft tissue engineering applications including liver tissues. [1,5,7,11,14,17,18,[27][28][29] For hepatocytes and hepatic cell lines that are presenti nl iver tissues, the spheroid morphology is critical towards maintaining high liver-specific functions. [30] However,t he trans-differentiation of hepatocytes into fibroblasts limits the culturingo fh epatocytes and still remains ac hallenge.…”
Section: Resultsmentioning
confidence: 99%